New characters and redescription of Dendroctonus vitei (Coleoptera: Curculionidae: Scolytinae). Issue 4 (21st March 2017) - Armendáriz-Toledano, Francisco; García-Román, Jazmín; López, María Fernanda; Sullivan, Brian T.; Zúñiga, Gerardo
Abstract: The taxonomic status of Dendroctonus vitei Wood (Coleoptera: Curculionidae: Scolytinae) and Dendroctonus mexicanus Hopkins is supported by biological and morphological data. However, the differentiation of these species has been extremely difficult because most of the morphological characters have not been well illustrated and some of them are geographically variable. Seminal rod shape has been the only reliable characteristic to identify these species. The main purpose of this study was to look for new morphological characters for the identification of these species as well as to evaluate geographic variation of those previously reported characters in order to produce a comprehensive redescription of D. vitei . A total of 33 morphological characters from antenna, stridulatory apparatus, male and female genitalia, and external morphology were compared between the similar species D. vitei and D. mexicanus, and we identified five novel diagnostic characters and confirmed previously reported characters that differentiate these two species from each other and from other species in the Dendroctonus frontalis Zimmermann complex ( sensu stricto ). Furthermore, these characters and those of the seminal rod allowed us to re-evaluate some previously reported records for other species to broaden the known distribution of D. vitei .